Towards personalized microbial therapies for metabolic alterations in celiac disease - Alejandro Borrego-Ruiz; Juan J. Borrego (Exploration of Digestive Diseases)
Celiac disease is an immune-mediated disorder with significant metabolic implications. Several factors have been proposed to explain the association between celiac disease in patients following a gluten-free diet and metabolic disorders, including metabolic syndrome. Growing evidence suggests a pivotal role of gut microbiome dysbiosis in the onset of celiac disease and its associated metabolic disturbances. The present narrative review examines (i) the connections between celiac disease and metabolism-related comorbidities, including metabolic syndrome and metabolic dysfunction-associated steatotic liver disease; (ii) the role of the gut microbiome in celiac disease, including the outcomes of gut microbiome dysbiosis in celiac children and adults; and (iii) the potential of microbial therapeutic strategies within the context of personalized medicine for patients with celiac disease and comorbid metabolic conditions. A synthesis of existing studies highlights several protective factors and interventions for future celiac disease prevention research. Adopting plant-based, health-promoting dietary patterns such as the Mediterranean or vegetarian diet within the first two years of life reduces celiac disease risk. These fiber- and phytochemical-rich diets support beneficial gut microbiota growth and short-chain fatty acid production, which maintain intestinal barrier integrity by enhancing mucus and tight junction proteins. Short-chain fatty acids also modulate immunity by inducing Tregs that secrete IL-10, suppressing pro-inflammatory Th1 responses and autoantibody production. Precision probiotics offer diverse therapeutic benefits in celiac disease by reducing inflammation, restoring beneficial microbes, and degrading immunogenic gliadin peptides. Postbiotics complement these effects by reinforcing barrier integrity and counteracting gliadin-induced inflammation. Thus, integrating clinical models with microbial biomarkers promises to improve celiac disease diagnosis and monitoring, enabling better risk stratification, earlier detection, and personalized management of this heterogeneous disease.